2020
DOI: 10.1155/2020/4087315
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 Mediates Lung Inflammation by the IL-6-Type Cytokine Oncostatin M

Abstract: The interleukin-1 family member IL-33 participates in both innate and adaptive T helper-2 immune cell responses in models of lung disease. The IL-6-type cytokine Oncostatin M (OSM) elevates lung inflammation, Th2-skewed cytokines, alternatively activated (M2) macrophages, and eosinophils in C57Bl/6 mice in vivo. Since OSM induces IL-33 expression, we here test the IL-33 function in OSM-mediated lung inflammation using IL-33-/- mice. Adenoviral OSM (AdOSM) markedly induced IL-33 mRNA and protein levels in wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Recruitment of neutrophils, eosinophils and inflammatory chemokines (KC, eotaxin-1, MIP1a and MIP1b), Th2 cytokines (IL-4/5), arginase-1 (M2 macrophage marker) and IL-33R+ ILC2s cells are significantly elevated in adenovirus Oncostatin M (OSM) mice, while these responses are significantly attenuated in IL-33-/- mice ( 113 ). In vitro , IL-33 upregulates OSM expression in RAW264.7 macrophage cells and bone marrow-derived macrophages ( 113 ). Thus, IL-33 is a key mediator of OSM-driven lung inflammation, induction of type 2 immune responses and M2 macrophages in mice, which contributes via activation of ILC2s ( 113 ).…”
Section: Crosstalk Between Ilc2s and M2 Macrophages In Lung Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recruitment of neutrophils, eosinophils and inflammatory chemokines (KC, eotaxin-1, MIP1a and MIP1b), Th2 cytokines (IL-4/5), arginase-1 (M2 macrophage marker) and IL-33R+ ILC2s cells are significantly elevated in adenovirus Oncostatin M (OSM) mice, while these responses are significantly attenuated in IL-33-/- mice ( 113 ). In vitro , IL-33 upregulates OSM expression in RAW264.7 macrophage cells and bone marrow-derived macrophages ( 113 ). Thus, IL-33 is a key mediator of OSM-driven lung inflammation, induction of type 2 immune responses and M2 macrophages in mice, which contributes via activation of ILC2s ( 113 ).…”
Section: Crosstalk Between Ilc2s and M2 Macrophages In Lung Diseasesmentioning
confidence: 99%
“…In vitro , IL-33 upregulates OSM expression in RAW264.7 macrophage cells and bone marrow-derived macrophages ( 113 ). Thus, IL-33 is a key mediator of OSM-driven lung inflammation, induction of type 2 immune responses and M2 macrophages in mice, which contributes via activation of ILC2s ( 113 ).…”
Section: Crosstalk Between Ilc2s and M2 Macrophages In Lung Diseasesmentioning
confidence: 99%
“…Subcutaneous injection of recombinant OSM led to skin inflammation in a murine model [ 13 ]. Botelho and colleagues [ 14 ] reported that overexpression of OSM resulted in lung inflammation in mice. Pothoven et al [ 10 ] reported that neutrophils are the main source of OSM in inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, in the tumor microenvironment, OSM has been reported to positively regulate EMT [ 52 ], degradation of ECM [ 53 ] and cell-substrate detachment of tumor cells [ 54 ], thus leading to metastatic transformation. According to our correlation analysis between OSM expression and specific immune cell infiltration, we make a point that the OSM-induced chronic inflammation may be mainly contributed by macrophages and neutrophils [ 4 , 55 57 ]. The regulations of various cells including tumor cells by OSM are extensively studied [ 58 60 ], however, enough shreds of evidence are still needed to demonstrate the relationship between OSM and diverse immune cells and the mechanisms.…”
Section: Discussionmentioning
confidence: 99%